Prevalence of Cardiovascular Disease and Associated Factors Among Type 2 Diabetes Patients in Selected Hospitals of Harari Region, Eastern Ethiopia - Regassa, Lemma Demissie; Tola, Assefa; Ayele, Yohanes (Frontiers in Public Health, 2021)
Background: Cardiovascular disease (CVD) is the most prevalent complication and the leading cause of death among patients with diabetes mellitus (DM). Type 2 diabetes mellitus (T2DM) patients have a 2- to 4-fold increased risk of CVD. There is a scarcity of data about the magnitude of CVD among patients with diabetes in Ethiopia. This study aimed to assess the prevalence and associated factors of CVD among T2DM patients at selected hospitals of Harari regional state of Ethiopia. Methods: This hospital-based retrospective data review was conducted among T2DM patients on follow-up in the diabetes clinics of selected hospitals of Harari regional state. The records of T2DM patients who have been diagnosed between January 1, 2013, and December 31, 2017, were reviewed from March to April 2018. Data were collected by using structured checklists from all necessary documents of T2DM patients. Statistical analysis was done using STATA 14.1. Bivariate and multivariate logistic regressions were used to identify factors associated with CVD. Result: The records of 454 T2DM patients were extracted from three government hospitals in Harari regional state. Their age was ranging from 15 to 86 years with a mean age (±SD) of 45.39 (14.76). The overall prevalence of CVD among T2DM patients was 42.51%, composed of hypertensive heart diseases (38.99%), heart failure (6.83%), and stroke (2.20%). The final multivariate logistic regression model revealed that age older than 60 years [adjusted odds ratio (AOR) = 3.22; 95% CI: 1.71–6.09], being physically inactive (AOR = 1.45; 95 CI: 1.06–2.38), drinking alcohol (AOR = 2.39; 95% CI: 1.17–6.06), hypertension (AOR = 2.41; 95% CI: 1.52–3.83), body mass index >24.9 kg/m2 (AOR = 1.81; 95% CI: 1.07–3.07), and experiencing microvascular diabetic complications (AOR = 3.62; 95% CI: 2.01–6.53) were significantly associated with the odds of having CVD. Conclusion: The prevalence of CVD was high and associated with advanced age, physical inactivity, drinking alcohol, higher body mass index, hypertension, and having microvascular complications. Health care workers should educate T2DM patients about healthy lifestyles like physical activity, weight reduction, blood pressure control, and alcohol secession, which can reduce the risk of CVD.